Diagnostic Concordance between Fine Needle Aspiration Cytology and Surgical Biopsy of Thyroid Nodules: A Retrospective Cross-Sectional Study from a Tertiary Referral Hospital in Riyadh, Kingdom of Saudi Arabia. (Global Journal of Medical Research, 2023)
Objective: To assess the diagnostic performance and yield of fine needle aspiration cytology (FNAC) of thyroid nodules.
Keywords: fine needle aspiration cytology; histopathology; sensitivity; negative predictive value; positive predictive value